Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bbr.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area cholinergic mechanisms mediate behavioral responses in the forced swim test

Abstract: Recent studies revealed a causal link between ventral tegmental area (VTA) phasic dopamine (DA) activity and pro-depressive and antidepressant-like behavioral responses in rodent models of depression. Cholinergic activity in the VTA has been demonstrated to regulate phasic DA activity, but the role of VTA cholinergic mechanisms in depression-related behavior is unclear. The goal of this study was to determine whether pharmacological manipulation of VTA cholinergic activity altered behavioral responding in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 81 publications
1
36
0
Order By: Relevance
“…These findings suggest that VTA mAChRs facilitate, but are not necessary for, cue-induced sucrose-seeking. Importantly, these Scop findings are not likely due to nonspecific motor effects, as we have previously demonstrated that VTA infusion of 24 μg Scop does not alter general locomotor activity [16]. Previous work also demonstrated that VTA Scop infusion does not alter operant responding in a progressive ratio task in rats that have already undergone operant acquisition training [13].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…These findings suggest that VTA mAChRs facilitate, but are not necessary for, cue-induced sucrose-seeking. Importantly, these Scop findings are not likely due to nonspecific motor effects, as we have previously demonstrated that VTA infusion of 24 μg Scop does not alter general locomotor activity [16]. Previous work also demonstrated that VTA Scop infusion does not alter operant responding in a progressive ratio task in rats that have already undergone operant acquisition training [13].…”
mentioning
confidence: 68%
“…Drug doses were selected based on our previous investigations demonstrating the ability of these doses to alter phasic DA release and behavior [6, 15]. Importantly, we previously showed that VTA infusion of 24 μg Scop, 30 μg Mec, or 1 μg AP-5 did not alter locomotor activity [6, 16]. …”
mentioning
confidence: 99%
“…After the 1 min drug infusion, the internal cannulae were left in place for an additional 1 min to allow for complete diffusion of drug into the brain tissue. Physostigmine (0, 1, or 2 μg, VWR, Bridgeport, NJ), an acetylcholinesterase inhibitor, and pilocarpine (0, 3, or 30 μg, Sigma Aldrich, St. Louis, MO), a selective mAChR agonist, were each dissolved in 0.9% saline and infused at behaviorally relevant doses that we and others have previously used in the VTA [2, 21, 42]. VTA infusion of vehicle or drug was performed immediately prior to the sucrose preference, elevated plus maze, forced swim or locomotor test session.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, findings from our laboratory and others have shown that VTA cholinergic mechanisms regulate both phasic DA cell firing and downstream phasic DA release in the NAc [14, 22, 38]. Furthermore, our recent findings revealed a novel role for cholinergic activity in the VTA in mediating both pro-depressive and antidepressant-like behavioral responses in the forced swim test (FST) [2]. However, it is unclear whether VTA cholinergic mechanisms also regulate other behavioral phenotypes associated with depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation